Complicated iatrogenic Cushing’s syndrome induced by topical clobetasol propionate in a child with psoriasis: a case report and review of the literature - Bahareh Abtahi-Naeini; Peiman Nasri; Kimia Afshar; Nikta Nouri (Journal of Medical Case Reports)
Abstract Background Long-term use of oral or parenteral corticosteroids is the most common cause of hypothalamic–pituitary–adrenal axis suppression and iatrogenic Cushing’s syndrome. Still, iatrogenic Cushing’s syndrome occurs rarely following the administration of topical corticosteroids. Case presentation This case study discusses the misuse of a high-potency corticosteroid cream by an Iranian 5-year-old male with plaque-form psoriasis, resulting in Cushingoid symptoms including moon face, buffalo hump, red striae, and weight gain. The child experienced different complications following iatrogenic Cushing’s syndrome, such as frequent vomiting and fever, which led to expiration. Conclusion Proper use and monitoring of topical corticosteroids are emphasized, especially among children. This study also underlines the potential side effects of high-potency corticosteroids and the importance of physicians’ and parents’ awareness, highlighting the avoidance of excessive topical corticosteroid prescriptions.